Utilization of shells of the snail Achatina fúlica Bowdich, 1822 (Mollusca, Gastropoda) by the hermit crab Clibanarius vittatus (Bosc, 1802) (Decapoda, Anomura) in the São Vicente Estuary, São Paulo, Brazil - Sanť, Bruno S. [UNESP]; Zangrande, Anna Cilene M. [UNESP]; Reigada, Alvaro L. D. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2005)
Hermit crabs depend on mollusc shells for housing. In this study, an unusual resource is reported for a hermit crab that usually inhabits marine gastropod shells. During a field study conducted from May 2001 to April 2003 in an estuarine area in São Vicente, state of São Paulo, Brazil, 21 individuals of Clibanarius vittatus (Bosc, 1802) were found inhabiting the shells of the terrestrial gastropod Achatina fullea Bowdich, 1822. A. fúlica occurs in nearshore grass patches, where occasional contact with sea water kills them, and their shells then become available to the hermit crabs.
Keywords: Anomura; Brazil; Clibanarius; Gastropoda; Hermit crab; Achatina; Achatina fulica; Clibanarius vittatus; Decapoda (Crustacea); Mollusca